(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the relationship between menstrual symptoms, psychological symptoms of menstruation, self-confidence, and mental readiness in female athletes. A total of 50 female athletes from various sports participated in this quantitative research. Data were collected using standardized questionnaires and analyzed using SPSS, including normality tests, linearity tests, and Pearson correlation analysis. The results showed that all variables were normally distributed and exhibited linear relationships. Correlation analysis revealed weak negative relationships between menstrual and psychological symptoms with self-confidence and mental readiness; however, none of the correlations reached statistical significance. The findings suggest that menstrual-related symptoms may not significantly impact psychological aspects of athletic performance, although individual variations exist. This study highlights the importance of considering both physical and psychological well-being in female athletes. Further research is recommended to explore psychological interventions that may enhance mental readiness and self-confidence during menstruation.